2022
DOI: 10.1016/j.amsu.2021.103211
|View full text |Cite
|
Sign up to set email alerts
|

Colorectal cancer survival rates in Makassar, Eastern Indonesia: A retrospective Cohort Study

Abstract: Background The 5-year overall survival (OS) rate for colorectal cancer (CRC) has been reported as 39%, and the 5-year recurrence-free survival (RFS) rate has been reported as 14%. Various prognostic factors have been associated with differences in survival rates among CRC patients. This study investigated the difference between several prognostic factors and the OS and RFS rates of CRC patients at the Dr. Wahidin Sudirohusodo General Hospital Makassar in Indonesia. Materials and met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 29 publications
1
8
0
Order By: Relevance
“…This proportion was also higher than reported from neighboring Southeast Asian countries, ie. 14.5% in Northern Malaysia and 5.7-13.4% in Singapore, as well as the 30-40% proportion previously reported from pathology and hospital-based data from Indonesia, demonstrating the higher incidence of EOCRC in the Asian population [8,[37][38][39][40].…”
Section: Discussionsupporting
confidence: 65%
See 1 more Smart Citation
“…This proportion was also higher than reported from neighboring Southeast Asian countries, ie. 14.5% in Northern Malaysia and 5.7-13.4% in Singapore, as well as the 30-40% proportion previously reported from pathology and hospital-based data from Indonesia, demonstrating the higher incidence of EOCRC in the Asian population [8,[37][38][39][40].…”
Section: Discussionsupporting
confidence: 65%
“…Colorectal cancer cases in Indonesia were dominated by males (54%), with a peak incidence at 50–54 years of age [ 7 ]. The local cases reported were also dominated by advanced tumors (30–40%) [ 6 , 8 ], all of which were associated with worse prognosis and decline in quality of life.…”
Section: Introductionmentioning
confidence: 99%
“…The survival rate of CRC patients in Indonesia is still rarely analyzed. Based on research conducted by Labeda et al, the OS of CRC patients was according to age, histopathology, stage, and history of definitive surgery [7]. Meanwhile, research conducted by Li stated that age, gender, tumor location, and histopathological type influenced the survival of CRC patients [8].…”
Section: Discussionmentioning
confidence: 99%
“…The International Agency for Research on Cancer (IARC) Global Cancer Observatory's GLOBOCAN 2018 database reported that the incidence of CRC in Indonesia was 30,017 out of 348,809 cancer cases, and it had the fifth-highest mortality rate (7.7%) among all cancers. [3][4] The role of inflammation in most tumours remains unclear while it is emerging as one of the hallmarks of cancer. Long-term treatment with non-steroidal anti-inflammatory drugs is remarkably effective in reducing cancer rate and death, indicates that inflammation might have many as-yet-unrecognized facets.…”
Section: Introductionmentioning
confidence: 99%